MENTAL HEALTH STATUS IN PATIENTS WITH STABLE CORONARY HEART DISEASE COMBINED WITH NON-ALCOHOLIC FATTY LIVER DISEASE - Vakalyuk, I.I. (The Ukrainian Scientific Medical Youth Journal, 2017)
Cardio-vascular disease remains the leading cause of death and disability in the population of the world and Ukraine, in particular. There are a number of factors, that contribute to increased cardio-vascular risk. Among them, the leaders are psycho-emotional disorders that cause an increase of cardiovascular mortality and reduce the overall assessment of the life quality of these patients. The aim of the study was to assess the mental health status of the patients with stable coronary heart disease (CHD) based on the presence and progression of non-alcoholic fatty liver disease (NAFLD). 300 patients with stable CHD were observed. Among them were 160 patients without NAFLD (Group I) and 140 patients with NAFLD (Group II). Among patients of Group II persons with non-alcoholic steatosis (Group IIA) and non-alcoholic steatohepatitis (NASH) (Group IIB) were observed. Assessment of mental health status was conducted by the Ukrainian versions of Hospital Anxiety and Depression Scale (HADS) and health questionnaire PHQ-15. Analysis of the results revealed clear patterns of modifications of the patient’s mental health depending on the availability and duration of NAFLD. In particular, in patients of Group I the total share of anxiety disorders was 65%. In the case of NAFLD the prevalence of depressive mental disorders was found. However, the most important manifestations as in percentage and clinical symptoms were observed in patients with NASH. Moreover, the total assessment score of patient health increased due to progression of anxiety and depression manifestations. Thus, the mental health of the patients with stable CHD was significantly affected by availability and progression of NAFLD. In particular, the absence of NAFLD in patients with stable CHD was characterized by the presence of anxiety-depressive mental disorder with prevalence of anxiety component. In the case of combined of stable CHD and NAFLD total share of mental disorders characterized by dominance of depressive disorders, the most pronounced in patients with NASH.